A comparative study on the dielectric functions of isolated Si nanocrystals and densely-stacked Si nanocrystal layer embedded in SiO2 synthesized with Si ion implantation - Ding, Liang (2011)
Both isolated Si nanocrystals (nc-Si) dispersedly distributed in a SiO2 matrix and densely stacked nc-Si layers embedded